Preventive interventions to reduce youth involvement in gangs and gang crime in low- and middle-income countries: a systematic review - Higginson, Angela (Campbell Systematic Reviews, 2015)
This Campbell systematic review examines why the implementation of preventive interventions to reduce youth involvement in gangs and gang crime may fail or succeed low and middle-income countries. The review summarises findings from four studies conducted in Latin America and the Caribbean. These include findings from field observations and interviews with 63 former gang members in Guatemala, Honduras and El Salvador, 940 respondents in three Jamaican communities, 24 participants in Nicaragua and 25 participants in Peru.